Spectral structure of a polycapillary lens shaped X-ray beam - Gogolev A. S. Aleksey Sergeevich; Filatov N. A. Nikolay Alexandrovich; Uglov S. R. Sergey Romanovich; Hampai D.; Dabagov S. B. (2018, 2018)
Title screen